Binge eating and personality traits: A gender-specific analysis among patients affected by obesity - Amelia RIzzo; Rossella Alfa; Alessia Giuffrida; Giuseppina Selene Spina; Veronica Currò; Maria Letizia Caracciolo (Advances in Medicine, Psychology, and Public Health)
Introduction: The literature has shown the inconsistency of the specific personality profile of the patients affected by obesity. However, most studies have focused on possible differences in personality traits between subjects with and without Binge Eating Disorder (BED), neglecting possible gender differences. The present work aims to study the relationship between eating behavior and personality traits in a sample of subjects affected by obesity with and without bingeing, considering biological sex. Methods: A total of 110 participants with BMI >35 kg/m², 30 males and 80 females, aged 18-60 years (M=38.70; SD=10.31) completed the Binge Scale Questionnaire (BSQ) for detecting the presence of binge eating (tot >9) and the Big Five Questionnaire (BFQ) for assessing personality traits. Results: Findings showed that no significant differences emerged when compared according to the presence or absence of the eating disorder (BED). In contrast, when gender was taken into consideration, the presence of BED in the male population was found to be associated with the sub-dimension "Impulse Control" (r=.263; p < 0.05) whereas in the female population it was correlated with the sub-dimension "Emotion Control" (r=-.206; p < 0.05) In addition, the trait Dynamism also emerged negatively correlated with the presence of binge eating in men and BMI in women. Conclusions: In conclusion, the personality areas that seem to be most involved in subjects with and without BED are ascribable to the sphere of Emotional Stability but suggest some differences between males and females, which deserve clinical attention and further studies